2001
DOI: 10.1055/s-2001-18821
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Recipient-Bed Isolation on Survival Rates of Skin-Flap Transfer in Rats

Abstract: The effect of recipient-bed isolation with artificial barriers on skin-flap survival, compared to flap transfer without bed isolation, was evaluated in a modified rat epigastric skin-flap model. The pattern of blood flow in the raised flap with a proximal axial portion and distal random portion was confirmed by laser Doppler flowmetry. Forty rats were divided into four groups. Three of the groups had one of three different artificial barriers-silicone, polypropylene, or gelatin sponge. In each of these three g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…In studies where bed isolation from an overlying flap with artificial sheets was examined, it has been shown that the survival rates of the flaps were significantly reduced compared to the flap survival rates in cases where flaps were transposed directly over the recipient bed. [28,29] The theory of revascularisation of the flap by the tissue of the recipient site either by inosculation or by connection of the vessels may be also supported.…”
Section: Discussionmentioning
confidence: 99%
“…In studies where bed isolation from an overlying flap with artificial sheets was examined, it has been shown that the survival rates of the flaps were significantly reduced compared to the flap survival rates in cases where flaps were transposed directly over the recipient bed. [28,29] The theory of revascularisation of the flap by the tissue of the recipient site either by inosculation or by connection of the vessels may be also supported.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies utilizing artificial barrier sheets, separation of the skin flap and the recipient bed caused worsening of flap necrosis. 29,30 These studies suggested a supportive role of the recipient bed as a supplying blood. Indeed, in our previous study, 6 gene transfer of bFGF to the recipient bed induced vessel formation from the recipient bed to the ischemic flap, and significantly improved blood perfusion of the flap.…”
Section: Discussionmentioning
confidence: 96%
“…FS also closely approximated and maintained the flap in the recipient bed. A study by Jones et al 27 demonstrated that separating the flap and the recipient site with an impermeable polypropylene sheet resulted in impaired flap healing. This suggests that the nonblocking porous structure of the FS increased flap adherence and decreased flap necrosis.…”
Section: Discussionmentioning
confidence: 99%